Three for Ajay: Learning at “The Other Side of Nowhere” - Watkins, Paul (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Paul Watkins reflects on his relationship with Ajay Heble, with particular focus on his work with the Improvisation, Community, and Social Practice project (ICASP).